1990
DOI: 10.2307/1541536
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Responses of the Blue Crab Callinectes sapidus to Long-Term Hypoxia

Abstract: Blue crabs (Callinectes sapidus) were held in hypoxic (50-55 mm Hg) water for 7-25 days. Postbranchial blood PO2 fell by about 80% within 24 h and then remained unchanged. Postbranchial blood total CO2 increased within 24 h and remained elevated for the duration of the experiment. There was no change in postbranchial blood pH, osmolality, or Cl. Lactate, urate, and Ca+2 all raise the O2 affinity of blue crab hemocyanin; by 25 days, blood lactate and urate had risen slightly, but Ca+2 had increased dramatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 38 publications
(38 reference statements)
2
56
0
Order By: Relevance
“…The [Hc] in the hemolymph of individual crabs was estimated with an established spectrophotometric method (Nickerson and Van Holde, 1971;deFur et al, 1990). An aliquot of serum was diluted by 50 mmol L -1 Tris HCl, containing 10 mmol L -1 EDTA, pH 8.9…”
Section: Hemocyanin Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The [Hc] in the hemolymph of individual crabs was estimated with an established spectrophotometric method (Nickerson and Van Holde, 1971;deFur et al, 1990). An aliquot of serum was diluted by 50 mmol L -1 Tris HCl, containing 10 mmol L -1 EDTA, pH 8.9…”
Section: Hemocyanin Concentrationmentioning
confidence: 99%
“…Halftimes for clearance of 125 I-labeled Hc have been reported to be 25.5 and 36 days in American lobster (Homarus americanus) and Caribbean spiny lobster (Panulirus argus) (Senkbeil and Wriston, 1981). A more rapid synthesis of Hc can be induced by various environmental factors, such as changes of ambient salinity (Gilles, 1977;Péqueux et al, 1979) and by moderate chronic hypoxia (Hagerman and Baden, 1988;deFur et al, 1990;Spicer and Baden, 2001).…”
Section: Effects Of Pot Fi Shing On Hemocyanin Concentrationmentioning
confidence: 99%
“…Numerous studies have shown that different sets of subunits determine distinct oxygen-binding affinities as evidence of the extensive functional variability (Mangum and Rainer, 1988;DeFur et al, 1990;Mangum, 1994;Spicer and Hodgson, 2003a,b). Also a plastic regulation of cooperative transition is provided by subunit heterogeneity as shown in P. interruptus.…”
Section: Subunit Diversity and Oxygen-binding Modulationmentioning
confidence: 99%
“…Moreover, while variations in Hc concentration are common to almost all Crustacea, the regulation of expression of individual monomers appears to be strictly species-related, and it conclusively accounts for the intra-specific Hc heterogeneity. In particular, it has been demonstrated that a change in Hc phenotype by means of differential expression of one or more subunits are a consequence of a defined physico-chemical stimuli and produces a shift in O 2 -binding affinity (Mason et al, 1983;Mangum and Rainer, 1988;DeFur et al, 1990;Mangum, 1994;Spicer and Hodgson, 2003b). This phenomenon has been intensely investigated in two species: the blue crab C. sapidus and the amphipod C. marinus.…”
Section: Relative Variation: Change In Subunit Compositionmentioning
confidence: 99%
See 1 more Smart Citation